Blockchain and Smart Contract for Digital Document Verification - Sunitha kumari, S.; Saveetha, D. (International Journal of Engineering and Technology, 2018)
Every year lakhs of students graduating from different university, after passing from university different students have different plans. All students who graduated will have different certificate such as marksheets, degree certificate, best performance certificate and etc. Some students have plans to get employed in companies or to do higher studies. Wherever students go they need submit the certificate for important reference. Due to lack of anti-forge mechanism some started to forge the certificate to get the employed or for further steps. In the digital certificate verification based on blockchain done only for the degree certificates. In the proposing system along with the degree certificate entire personality and behaviour activities of the person using personal id will be uploaded in blockchain. Because of unmodifiable property it is stored in block chain. Initially the student request for the e-certificate by uploading certificate or personal id to electronic certificate system. If requesting for e-cert then the system will review certificate from the university or schools or from organization and get the assurance and store the serial number and e-certificate to the block chain. The system will be generating the QR code and send it to the user. when applying for company user will send only the certificate serial number and QR code received from the e-certificate company.Â Â